2010
DOI: 10.1161/strokeaha.109.571935
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress After Thrombolysis-Induced Reperfusion in Human Stroke

Abstract: Background and Purpose-Animal models of transient ischemia suggest that oxygen-derived free radicals produced on reperfusion of ischemic brain could constitute the main cause of reperfusion injury. We aimed to determine the presence and role of lipid peroxidation and protein oxidation-related molecules after tissue plasminogen activator-induced recanalization in human stroke. Methods-A total of 160 patients with strokes involving the middle cerebral artery and treated with tissue plasminogen activator and 60 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 35 publications
2
65
2
4
Order By: Relevance
“…Studies in the field of oxidative stress and clinical implications revealed that generation of free radicals prompting oxidative stress plays a role in pathogenesis of the brain injuries (13). In normal condition, oxidants and antioxidants are in a balance status (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the field of oxidative stress and clinical implications revealed that generation of free radicals prompting oxidative stress plays a role in pathogenesis of the brain injuries (13). In normal condition, oxidants and antioxidants are in a balance status (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…In subjects with juvenile AMI in whom we investigated plasma lipid peroxidation, expressed as TBARS, and plasma protein oxidation, expressed as carbonyl groups, a marked increase in both parameters was found at the initial stage of AMI [39,40]. The same behavior was present in AIS patients, in whom the increase in lipid peroxidation and protein oxidation, besides being evident at admission and 24 hours later [41], persisted for some months after the onset of AIS [42].…”
Section: Conclusive and Pharmacological Considerationmentioning
confidence: 93%
“…Nađeno je (Grafik 1a) da je aktvinost MPO u serumu za oko 50% veća u grupi sa IMU u odnosu na kontrolnu grupu (67.2 U/L vs. 92.3 U/L, kod kontrole i kod pacijenata; p < 0.05). Iako za sada u literaturi ne postoje podaci o hlorinišućoj aktivnosti ekstracelularne MPO kod pacijenata sa IMU, Cojocaru i saradnici su našli za oko 30% veće koncentracije proteina MPO u serumu u akutnoj fazi IMU [11], dok je u jednoj drugoj studiji koncentracija MPO bila dvostruko veća od kontrolnih vrednosti [16].…”
Section: Diskusijaunclassified
“…Aleksandrova i saradnici su pokazali da iako je broj neutrofila bio proporcionalan težini IMU, sposobnost aktivacije, degranulacije i stvaranja oksidanasa nisu odgovarali kliničkoj težini bolesti [15]. U studiji Dominguez i saradnika nije bilo nikakve korelacije koncentracije MPO sa NIHSS skorom, kao pokazateljem kliničke težine bolesti [16]. Ni u našoj studiji nije postojala statistički značajna korelacija između NIHSS skora i MPO aktivnosti, kao ni između MPO aktivnosti i koncentracije hloramina (Tabela 3).…”
Section: Diskusijaunclassified